KAJIAN LITERATUR PEMANFAATAN ADSORBEN ARANG AKTIF LIMBAH ORGANIK TERMODIFIKASI SURFAKTAN (SLS/SDS) TERHADAP ION LOGAM BERAT - Terra, Patrycia Zulliani; Yusuf, Bohari; Lianasari, Ika Yekti (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
A literature review of the use of surfactant-modified organic waste activated charcoal adsorbents (SLS/SDS) on the percent absorption and adsorption capacity of heavy metal ions has been carried out. The surfactants used are sodium lauryl sulfhate (SLS) and sodium dodecyl sulfhate (SDS). The organic waste activated charcoal used includes rice husks, teak wood sawdust, bamboo, salak fruit skin and coconut shells. From this study, it was found that activated charcoal predominantly contains cellulose and its derivatives which can be a carbon source. Modification with surfactants (SLS/SDS) aims to increase the adsorption capacity, absorption percentage and also the surface area of the adsorbent. The modification process is by mixing surfactant and activated charcoal with a certain weight and then homogenizing. The mixture was then neutralized with distilled water. Next, it is placed in the oven at a certain temperature, then crushed and sieved with a 100 mesh size. Next, the activated charcoal-surfactant adsorbent is contacted with heavy metal ions such as Pb2+, Cr3+, Cr6+, and Ni2+. The absorption results obtained ranged from 93.50 – 99.89%, with an adsorption capacity of 0.144 – 81.300 mg/g. The size of the percent absorption value and adsorption capacity is influenced by the surface area, activator substance, contact time, pH, and also the concentration of the adsorbate. Keywords: Activated Charcoal, Heavy Metal Ions, SLS, SDS, Modification